Sociolinguistic Characterization of Métis People in Canada - V. A. Kozhemyakina (Научный диалог, 2024)
This article presents a sociolinguistic characterization of the indigenous Métis people in Canada. Drawing on existing scholarly works and research, the study aims to describe the status of the Métis people, recently recognized as an indigenous nation of the country, and their language. It delves into the historical formation of the Métis nation and its current state, providing a demolinguistic profile of the Métis population today. Statistical data from recent censuses is included. The novelty of this research lies in its examination of the contemporary situation of the Métis people with a focus on existing laws and judicial decisions impacting all aspects of their lives. An overview of anthropological and sociolinguistic studies on Métis people conducted by scholars over the past decades is offered. The author emphasizes the functional characteristics of the Métis language, Michif, outlining its ethnic and social functions. The article also discusses policies concerning Métis people in the realms of social, economic, and political rights. The relevance of this study is underscored by the heightened attention from Russian and global societies towards language situations and solutions to linguistic issues in polyethnic states, as well as the preservation of indigenous languages.